2011
DOI: 10.1111/j.1743-6109.2011.02257.x
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Decreases the Genital Vascularization in Young Healthy, Eumenorrheic Women

Abstract: Introduction Cigarette smoking is a major health hazard and may impair the normal sexual response. Aim To evaluate (in the early follicular phase, and independently from sexual stimulation) in young, eumenorrheic, healthy, lean women the general and genital vascular effects of the smoking habit. Methods One hundred thirty-seven patients undertook, in the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…Multivariate analysis mentioned that hypertension (OR = 5.4), diabetes mellitus (OR = 5.4) and smoking (OR = 3.1) were significant risk factors for erectile dysfunction (ED). [62] Also, Battaglia et al [63] mentioned that cigarette smoking could decrease central and peripheral tissue perfusion and increase the risks of genital vessel stiffness and impaired sexual performance and cause an erectile disorder. Furthermore, Johannes et al [64] stated that depression is significantly associated with self-reported sexual functioning as approximately 40% of sexual arousal disorders participant reported having concurrent depression.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analysis mentioned that hypertension (OR = 5.4), diabetes mellitus (OR = 5.4) and smoking (OR = 3.1) were significant risk factors for erectile dysfunction (ED). [62] Also, Battaglia et al [63] mentioned that cigarette smoking could decrease central and peripheral tissue perfusion and increase the risks of genital vessel stiffness and impaired sexual performance and cause an erectile disorder. Furthermore, Johannes et al [64] stated that depression is significantly associated with self-reported sexual functioning as approximately 40% of sexual arousal disorders participant reported having concurrent depression.…”
Section: Discussionmentioning
confidence: 99%
“…For both women and men, it may be expected that the amount of alcohol consumed would influence the quality of the sexual activity (McKay, 2005). In fact, alcohol consumption may be conceptualized as having an even greater influence on men's perceptions of quality of sexual intercourse compared with women as situational erectile impairments resulting from excessive alcohol consumption are somewhat common (Laumann et al, 1999;Rosen, 1991), yet alcohol consumption is not associated with a reduction in vaginal lubrication in women (Battaglia et al, 2011). Perhaps the negative association between the number of alcoholic drinks consumed and quality of sexual intercourse emerged among women because as intoxication level increased along with the number of drinks consumed, women may have had a less clear perception of their sexual activity and behaviors in general and thus ranked it as lower quality.…”
Section: International Journal Of Sexual Healthmentioning
confidence: 97%
“…The 3D power Doppler histogram analysis of clitoral and labium minus blood flow showed the worst vascular indices, the vascularization index, the flow index, and the vascularization flow index of clitoral body and labia minora in the heavy smokers. The authors concluded that cigarette smoking may be associated with a reduced central and peripheral tissue perfusion with consequent increased risk of cerebrovascular and CVDs, and with genital vessels stiffness and reduced sexual function [13].…”
Section: Female Sexual Function and Dysfunctionmentioning
confidence: 99%